Conveyor system in transfer line - Ab Rahman, Asma Azlaily; Zulkifli, Norlidayu; Yazid, Siti Saerah; Abd Hadi, Nurul Shafieka; Rajemi, Mohamad Farizal (2013)
Conveyor systems used in the transfer line to help ease the work done. In the process of television production conveyor system is used to facilitate and accelerate the product produced.In production television, rubber belt conveyor are uses for transfer to electronic component’s part that is Printed Circuit Board (PCB).This conveyor are uses because component electronic very sensitive because component PCB is used to mechanically support and electrically connect electronic components such as capacitors, resistors or active devices have been manufactured into the board. So, by using conveyors belt system are suitable for this movement component television because conveyor belt move in speed appropriate and this situation save the component television like PC Board from damage.In television production, belt conveyor used due to the ease of movement of the visual inspection station to station assembly.There are advantages obtained when the rubber conveyor belt used in the process to produce a television.However there are also some problems when using the conveyor in production television.